The association between upward and downward earnings management and equity liquidity: empirical evidence from non-financial firms listed in Vietnam - Quynh Lien Le; Hanh Hong Ha; Thi Minh Phuong Nguyen; Thuy Duong Doan (Cogent Business & Management, 2023)
The current study aims at examining the impact of earnings management on equity liquidity in the Vietnam stock market when considering the direction of earnings management. We used two proxies of equity liquidity, namely quoted spread and effective spread, and analyzed the data using ordinary least squares (OLS), fixed and random effect models (FEM, REM), and regression with generalized least squares (GLS) to determine the most suitable model. The findings of the study indicate that when downward earnings management increases, the quoted spread also decreases, thus the bid-ask spread is low, meaning that the liquidity is high. This can be explained by the fact that when firms conduct downward earnings management to reduce taxes, investors may expect to buy stocks from these firms at a better price, leading to an increase in trading demand on the market. Whereas upward earnings management has no impact on quoted spread. Our results also showed that there is no evidence to suggest that earnings management has an impact on the effective spread. This means that, in the absence of other factors, an increase in earnings management in either upward or downward directions does not affect the difference between buying and selling prices.
Keywords: 650; earnings management; earnings management and equity liquidity; equity liquidity; non-financial firms